Pengaruh Kesejahteraan Karyawan dan Pelatihan terhadap Produktivitas Pekerja di Perusahaan PT. Hayyu Pratama Kaltim - Dona Bonita; Jubaidi Jubaidi; Achmad Effendi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the effect of employee welfare and training on worker productivity at PT. Hayyu Pratama Kaltim. Welfare and training are considered important factors in improving employee performance, especially in construction service companies with high workloads. This research uses a descriptive quantitative approach, with data collected through questionnaires distributed to 48 randomly selected respondents. Data analysis was conducted using multiple linear regression with the help of SPSS version 27. The results show that employee welfare and training have a positive and significant effect on worker productivity, both partially and simultaneously. The coefficient of determination (R²) of 41.6% indicates that these two variables explain a significant portion of the variation in employee productivity. These findings suggest that efforts to improve productivity should be supported by appropriate welfare and training programs.